African migration and the novel exploring race, civil war, and environmental destruction - Taylor, Jack 1982- (University of Rochester Press, 2024)
Examines how current novels dealing with African migration address social issues, immigrant subjectivity, and the politics of migration. African Migration and the Novel: Exploring Race, Civil War, and Environmental Destruction explores pressing social and political issues such as racial identity, environmental devastation, human trafficking, and political violence through the lens of novels of African migration. The book details how authors such as Chika Unigwe, Chris Abani, Dinaw Mengestu, In Koli Jean Bofane, Boubacar Boris Diop, and others develop "the migratory imagination": the creative means mobilized within their novels to expose the reader to contemporary social issues. Drawing on and synthesizing a multitude of theoretical frameworks including ecocriticism, postcolonial theory, genre studies, Black studies, paratextual reading, and political economy, the book argues for the flexibility of the migration novel as a genre. African Migration and the Novel traces migratory routes such as Nigeria to London and Belgium, Congo to Paris, Ethiopia to Washington, DC, and internal migration resulting from environmental destruction in Sierra Leone, while paying deep attention to the historical and political conditions described in the novels. The subjectivities and livelihoods of immigrants, refugees, those living in exile, and asylum seekers are all represented in the migration novels under discussion. Ultimately, this work demonstrates the promise of the African migration novel to awaken a sense of justice in the reader
Title from publisher's bibliographic system (viewed on 10 May 2024)
Introduction: The Migratory Imagination -- Migration, Sexual Exploitation, and the Form of the Afterlife of Slavery: Chika Unigwe's On Black Sisters Street and Chris Abani's Becoming Abigail -- Refugee Livelihood, Racial Disorientation, and Mourning and Melancholy: Dinaw Mengestu's The Beautiful Things that Heaven Bears and How to Read the Air -- Hospitality, Forgiveness, and the Afterlife of Colonialism in the Paris Suburbs: Wilfried N'SondeÌ's The Heart of the Leopard Children and The Silence of Spirits -- Migration and the Rwanda Genocide: Boubacar Boris Diop's Murambi: The Book of Bones and Gilbert Gatore's The Past Ahead -- Environmental Devastation and Accumulation by Dispossession: Ishmael Beah's Radiance of Tomorrow and In Koli Jean Bofane's Congo INC.
Keywords: Emigration and immigration in literature; Immigrants in literature; African diaspora in literature; Africans / Migrations; Schriftsteller; Migration; Auswanderung -- Motiv; Afrikaner; Africa / Emigration and immigration